Pengaruh motivasi dan minat belajar terhadapPrestasi belajar siswa pada kelas tinggiSd negeri 01 tempursari tahunAjaran 2015/2016 - Sari, Ana Purnama; , Drs. Risminawati, M.Pd (2016)
The purpose of this study was to determine:(1) the effect of motivation on student achievement in high class SD Negeri 01 Tempursari Academic Year 2015/2016, (2) to determine the effect of learning interest on student achievement in high class SD Negeri 01 Tempursari Academic Year 2015 / 2016, (3) to determine the effect of motivation and interest in learning on student achievement in high class SD Negeri 01 Tempursari Academic Year 2015/2016. This type of quantitative research with type of ex post facto. This research was conducted in the Elementary School I Tempursari, with a population of grade IV, V, and VI totaling 69 students, this research is a population study. The data collection technique used is the technique of questionnaires and documentation. Prerequisite test used is the test for normality and linearity. Data analysis technique used is multiple linear regression analysis, hypothesis testing using t test, F test, the relative contribution and effective contribution. The results showed regression line equation: Y = 46,279 + 0,115.X₁ + 0,139.X₂. (1) The first hypothesis test results are positive effect of motivation on learning achievement, indicated by tcount 3,036 > ttable 1,995 and signfikansi value < 0.05, namely 0.003. (2) Results of testing the second hypothesis there is positive interest in learning to learning achievement, indicated by tcount 3,411 > ttable 1,995 and signfikansi value < 0.05, namely 0.001. (3) Testing of the third hypothesis there are positive influence between motivation and interest in learning to learning achievement, indicated by Fcount 29,178 > Ftable 3,15 with significant value 0.000 < 0.05. The coefficient of determination (R²) of 0,469, or 46,9 %, meaning that student achievement is influenced by motivation and interest in learning by 46,9 %, while the remaining 53,1 % is influenced by other variables.